2014
DOI: 10.1515/pr-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Polite appearances: How non-manual features convey politeness in British Sign Language

Abstract: This paper explores how non-manual features are key to conveying linguistic politeness in British Sign Language (BSL). Data were collected through five semi-structured interviews incorporating the elicitation of two speech acts commonly associated with research on linguistic politeness: requests and apologies. The data from this exploratory study suggest that nonmanual features (including specific mouth gestures and movements of the head and upper body) are more crucial for linguistic politeness than manual si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This supported triangulation of the data, both within and between the two participant groupings. Coding categorisations were either theory-or data-driven (Braun and Clark 2006) with some theory-driven codes based on earlier research on politeness features in BSL (Mapson 2014a). Initial coding included in vivo terms, those generated by participants (Charmaz 2006), where possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This supported triangulation of the data, both within and between the two participant groupings. Coding categorisations were either theory-or data-driven (Braun and Clark 2006) with some theory-driven codes based on earlier research on politeness features in BSL (Mapson 2014a). Initial coding included in vivo terms, those generated by participants (Charmaz 2006), where possible.…”
Section: Discussionmentioning
confidence: 99%
“…There can be a tendency for studies to reinforce inaccurate cultural stereotypes (Tanaka et al 2008), failing to recognise subtle cultural differences (Aoki 2010) and intra-cultural variation (Hernandez-Flores 1999). This is evident in the association of a lack of indirectness with deaf culture in the USA (Mindess 2006), which is challenged by other studies that evidence how indirectness is conveyed through non-manual markers involving facial expression and the upper body (Ferreira Brito 1995, Roush 2007, Hoza 2007, George 2011, Mapson 2014a.…”
Section: Cross-cultural and Intercultural Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghana, polite behavior is more identified with greetings, use of titles and honorifics, use of the words "please" and "thank you," use of a soft voice, and be quiet if necessary. (Thompson & Anderson, 2019) Slightly different from Ghanaians, parents in Japan usually give first HERITAGE OF NUSANTARA: INTERNATIONAL JOURNAL OF RELIGIOUS LITERATURE AND HERITAGE 253 assignments to children under five years of age to exercise courage, independence, and responsibility (Setiawati, 2020) because children must do the first task without help from their parents. Bugis culture, such as "Siri," can also be applied, teaching students to be individuals with high self-esteem.…”
Section: Literatur Review Character Valuesmentioning
confidence: 99%
“…(Santoso et al, 2020b;Prasetiyo et al, 2020) Ghana, polite behavior is more identified with greetings, use of titles and honorifics, use of the words "please" and "thank you," use of a soft voice, and be quiet if necessary. (Thompson & Anderson, 2019) Slightly different from Ghanaians, parents in Japan usually give first HERITAGE OF NUSANTARA: INTERNATIONAL JOURNAL OF RELIGIOUS LITERATURE AND HERITAGE 253 assignments to children under five years of age to exercise courage, independence, and responsibility (Setiawati, 2020) because children must do the first task without help from their parents. Rokhman et al (2014) define character education as a process of accumulating knowledge and wisdom to create a good life for humans.…”
Section: Literatur Review Character Valuesmentioning
confidence: 99%